Redlight, Greenlight- Fedsure Life Assurance v Greater Johannesburg Transitional Metropolitan Council, Premier, Mpumalanga v Executive Committee, Association of State-Aided Schools, Eastern Transvaal - Klaaren, Jonathan (Juta, 1999)
Commentary on the administrative law aspects of two decisions heard in the Constitutional Court. Does the right of administrative justice found an independent cause of action or one that is co-extensive with judicial review on administrative law principles.
Keywords: Constitutional law; Administrative law; Constitutional court; Procedural fairness; Administrative justice